A Dictionary without Definitions: Romanticist Science in the Production and Presentation of the Grimm Brothers' German Dictionary, 1838–1863. Issue 4 (13th November 2014) - Kistner, Kelly
Argument: Between 1838 and 1863 the Grimm brothers led a collaborative research project to create a new kind of dictionary documenting the history of the German language. They imagined the work would present a scientific account of linguistic cohesiveness and strengthen German unity. However, their dictionary volumes (most of which were arranged and written by Jacob Grimm) would be variously criticized for their idiosyncratic character and ultimately seen as a poor, and even prejudicial, piece of scholarship. This paper argues that such criticisms may reflect a misunderstanding of the dictionary. I claim it can be best understood as an artifact of romanticist science and its epistemological privileging of subjective perception coupled with a deeply-held faith in inter-subjective congruence. Thus situated, it is a rare and detailed case of Romantic ideas and ideals applied to the scientific study of social artifacts. Moreover, the dictionary's organization, reception, and legacy provide insights into the changing landscape of scientific practice in Germany, showcasing the difficulties of implementing a romanticist vision of science amidst widening gaps between the public and professionals, generalists and specialists.